Website Quality, Brand Image, Brand Trust, Repurchase Intentions, and Customer Satisfaction - Ni Komang Meita Sari; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
This study investigates the relationship between website quality, brand image, brand trust, customer satisfaction, and repurchase intentions. This study specifically looks at the function of customer satisfaction as an influencing factor. The data collection technique in this study was a questionnaire using the Google Form platform which was distributed directly to all Goldmine Coffee Sunrise consumers using a QR Code. Based on a sample of 150 respondents, the results of the direct influence study show that website quality and brand image affect repurchase intentions. On the other hand, direct influence research shows that brand trust and customer satisfaction have no effect on repurchase intentions, and indirect effects show website quality, brand image, and brand trust do not affect repurchase intentions through customer satisfaction. This research supports the theory of consumer behavior and contributes to the marketing management literature by recognizing that website quality and brand image are important in consumer purchasing decisions. This research also contributes to providing a different view of brand trust and customer satisfaction which shows that consumer trust and satisfaction do not always generate an intention to make a repeat purchase.